Implications of the 2020 Global Food Policy Report for Eurasia Region: The Case of Armenia - Urutyan, Vardan (2020)
Vardan Urutyan GLOBAL FOOD POLICY REPORT Virtual Event--Discussion on the Implications of the 2020 Global Food Policy Report for Eurasia Co-Organized by the Eurasian Center for Food Security at Lomonosov Moscow State University, Westminster International University in Tashkent, the World Bank Group, and IFPRI MAY 27, 2020 - 02:30 PM TO 04:00 PM MSK